Maternal and perinatal outcome in a pregnancy with nephrotic syndrome - Mishra, Vineet; Agarwal, Himani; Lamba, Sunita; Chaudhary, Sumesh; Roy, Priyankur; Goel, Sugandha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The influence of pregnancy on the subsequent course of pre-existing nephrotic syndrome is controversial as also the effect of membranous glomerulonephritis on maternal and perinatal outcome. We describe a case of successful pregnancy outcome in Hepatitis B reactive patient with pre-existing nephrotic syndrome (renal biopsy proven case of Membrano-proliferative Glomerulonephritis). She had regular nephrology consultation and her renal disease was well compensated. After sonographic confirmation of live intrauterine pregnancy at 9th gestational week, patient was given methylprednisolone (5mg once daily). Antihypertensive drugs were also given. At 35 weeks of gestation, patient went in labour and cesarean section was performed in view of previous caesarean section. Feto-maternal outcome was good. The intrapartum and postpartum period was uneventful. Renal functions were well preserved. A vigourous healthy 1.93 kg baby was discharged with mother in a stable condition after receiving hepatitis B immunoglobulin.